PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3), MOTIVASI KERJA, DAN EFIKASI DIRI TERHADAP KINERJA KARYAWAN ( STUDI KASUS PADA PT BPR JAYA KERTI DENPASAR) - I Komang Windu Sandika; I Wayan Widnyana; I Made Sukadana (EMAS, 2023)
Human resources are one of the important factors of a company and have a role that determines the development of the company. Humans are the main asset in an organization or company that needs serious attention and needs to be managed properly. This is intended so that the human resources that are owned can be produced by the company and are able to provide maximum contribution so that they can produce a quality performance in the context of achieving company goals. This study aims to analyze the effect of occupational safety and health (K3), work motivation, and self-efficacy on employee performance at PT BPR Jaya Kerti Denpasar. This research was conducted at PT BPR Jaya Kerti Denpasar with several employees as respondents. The type of data used in this research is qualitative and quantitative data. While the source uses primary and secondary data. With the number of samples taken as many as 41 respondents with the census method. This data was collected by means of observation, interviews, questionnaires, and literature. These data were analyzed using multiple linear regression analysis assisted by the SPSS version 25 program. The results of this study indicate that the variables of occupational safety and health, work motivation, and self-efficacy have a positive and significant effect on employee performance.